2011
DOI: 10.1007/s11010-011-0996-x
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the Orange domain of E(spl)-M8, and the roles of the C-terminal domain in autoinhibition and Groucho recruitment

Abstract: CK2 is a Ser/Thr protein kinase that regulates the activity of the Drosophila basic-helix-loop-helix (bHLH) repressor M8 encoded by the Enhancer of split Complex (E(spl)C) during neurogenesis. Specifically, phosphorylation appears to elicit a conformational change in an autoinhibited state of M8 to one that is permissive for repression. We describe biochemical and molecular modeling studies that provide new insights into repression by M8. Our studies implicate the phosphorylation domain in autoinhibition, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Our demonstration that Da AD1 interacts with the Orange domain of E(spl) proteins adds a new function to that elusive domain, which defines the bHLH-O subfamily and to date has been implicated in dimerization (21,65) and Sens binding (31). The recently proposed structure of the Orange domain as a dimeric hairpin of two ␣ helices (Protein Data Bank accession number 2DB7) is consistent with both its role in dimerization and its role as a protein interaction surface.…”
Section: Discussionsupporting
confidence: 71%
“…Our demonstration that Da AD1 interacts with the Orange domain of E(spl) proteins adds a new function to that elusive domain, which defines the bHLH-O subfamily and to date has been implicated in dimerization (21,65) and Sens binding (31). The recently proposed structure of the Orange domain as a dimeric hairpin of two ␣ helices (Protein Data Bank accession number 2DB7) is consistent with both its role in dimerization and its role as a protein interaction surface.…”
Section: Discussionsupporting
confidence: 71%
“…5E). The crystal structure of the Hey1 Orange motif suggested that Orange motif monomers can dimerize (Protein Data Bank [PDB] file 2DB7) (Eastwood et al 2011 revealed significant homology among the residues located at the interaction interface of Orange monomers (Fig. 5F, highlighted in green).…”
Section: Insb Antagonizes Dpn Activity Through Protein Sequestrationmentioning
confidence: 99%
“…Like the HLH domain, the Orange domain consists of two amphipathic alpha-helices and mediates protein-protein interactions, including dimerization of the basic helix-loop-helix-orange (bHLH-O) proteins, where it acts as an "extension" of the HLH domain (Dawson, Turner, Weintraub, & Parkhurst, 1995;Eastwood, Yin, Bandyopadhyay, & Bidwai, 2011;Knust et al, 1992;Taelman et al, 2004;Zarifi et al, 2012). Like the HLH domain, the Orange domain consists of two amphipathic alpha-helices and mediates protein-protein interactions, including dimerization of the basic helix-loop-helix-orange (bHLH-O) proteins, where it acts as an "extension" of the HLH domain (Dawson, Turner, Weintraub, & Parkhurst, 1995;Eastwood, Yin, Bandyopadhyay, & Bidwai, 2011;Knust et al, 1992;Taelman et al, 2004;Zarifi et al, 2012).…”
Section: E(spl): From a Spontaneous Dominant Mutation To A Group Of Cmentioning
confidence: 99%